Serum Biochemistry and Inflammatory Cytokines in Racing Endurance Sled Dogs With and Without Rhabdomyolysis - Frye, Chris W.; Mann, Sabine; Joseph, Jodie L.; Hansen, Cristina; Sass, Brent; Wakshlag, Joseph J. (Frontiers in Veterinary Science, 2018)
Serum muscle enzymes in endurance sled dogs peak within 2-4 days of racing. The object of this study was to compare mid-race serum chemistry profiles, select hormones, and markers of inflammation and the acute phase response in dogs that successfully completed half of the 2015 Yukon Quest sled dog race (n = 14) and those who developed clinical exertional rhabdomyolysis (ER) (n = 5). Concentrations of serum phosphorus in ER dogs were moderately elevated compared to healthy dogs (median 5.5 vs. 4.25 mg/dL, P = 0.001) at mid race. ALT, AST, and CK show a marked increase from pre-race baseline to mid-race chemistries (P < 0.01), with more pronounced increases in dogs with ER compared to healthy racing dogs (median 46,125 vs. 1,743 U/L; P < 0.001). Potassium concentrations were moderately decreased from pre-race baselines in all dogs (median 5.1 vs. 4.5mEq/L; P < 0.01), and even lower in dogs with ER (median 3.5 mEq/L; P < 0.001) mid-race. No changes in serum pro-inflammatory cytokine concentrations were noted in any groups of dogs. C-reactive protein was elevated in both groups of dogs, but significantly higher in those with ER compared with healthy dogs mid-race (median 308 vs. 164 ug/mL; P < 0.01). Dogs with clinical ER may exhibit CK elevations of 50 times the upper limits of normal, while healthy dogs may have CK elevations over 10,000 U/L. Although potassium decreases in healthy endurance sled dogs, it remains in the normal laboratory reference range; however ER dog potassium levels drop further to the point of hypokalemia. Such an electrolyte disturbance may predispose these dogs to developing ER. Lastly increases in CRP may be reflective of a physiological response to exercise over the course of a race; however high CRP in ER dogs may be capturing an early acute phase response from myonecrosis.